2022
DOI: 10.1002/hon.2962
|View full text |Cite
|
Sign up to set email alerts
|

TAFRO syndrome with fatigue and abdominal distension as the first symptom: A case report

Abstract: TAFRO syndrome is a peculiar and rare type of multi‐centric Castleman's disease which contained a series of symptoms such as thrombocytopenia (T), anasarca (A), fever (F), reticulin fibrosis (R), and organomegaly (O). Here we provide a case of TAFRO syndrome with the manifestation of fatigue, abdominal distension, and low fever at primary diagnosis, characterized by multiple lymphadenopathy of superficial mediastinal and retroperitoneal lymph nodes, and it was finally confirmed by lymph node biopsy. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The efficacy of rituximab has also been verified in pediatric patients. 68 Some case reports have shown that the use of the R-CHOP regimen (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone), 69,70 as used for invasive B-cell lymphoma, can inhibit an overactivated immune system and prevent the occurrence of a cytokine storm. In a retrospective study from China, five patients received CHOP/COP-like chemotherapy as the first-line treatment, among whom two patients also received rituximab; all patients eventually died due to disease progression and drug-related toxicity.…”
Section: Rituximabmentioning
confidence: 99%
“…The efficacy of rituximab has also been verified in pediatric patients. 68 Some case reports have shown that the use of the R-CHOP regimen (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone), 69,70 as used for invasive B-cell lymphoma, can inhibit an overactivated immune system and prevent the occurrence of a cytokine storm. In a retrospective study from China, five patients received CHOP/COP-like chemotherapy as the first-line treatment, among whom two patients also received rituximab; all patients eventually died due to disease progression and drug-related toxicity.…”
Section: Rituximabmentioning
confidence: 99%